1999
DOI: 10.3346/jkms.1999.14.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 gene mutation in tumor aggressiveness of intracranial meningiomas

Abstract: The mutations that occur in the p53 tumor suppressor gene have been studied in various human malignant tumors. However, little is known about this gene in meningiomas. To investigate the relationship and frequency of p53 gene mutations, the p53 polymerase chain reaction-single stranded conformational polymorphism (PCR-SSCP) and immunohistochemical study were performed on the 41 intracranial meningiomas (21 benign, 11 atypical, and 9 malignant). The higher the p53 protein expression rate, the poorer the histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 0 publications
6
39
0
Order By: Relevance
“…Interestingly, the p53 LI and histoscore (but not the labelling intensity) has an inverse correlation with the chance of recurrence in the WHO grade I tumours in our study, but if we examine all the WHO grades, the increased staining in the higher grades, changes to forward proportion, similarly to prior studies [7,14,15]. This may be explained by the fact that the p53 immunoreactivity does not distinguish between the wild type (WT) and mutant protein; in non-recurrent cases increased normal protein may have a beneficial effect as p53 is involved in DNA damage repair.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Interestingly, the p53 LI and histoscore (but not the labelling intensity) has an inverse correlation with the chance of recurrence in the WHO grade I tumours in our study, but if we examine all the WHO grades, the increased staining in the higher grades, changes to forward proportion, similarly to prior studies [7,14,15]. This may be explained by the fact that the p53 immunoreactivity does not distinguish between the wild type (WT) and mutant protein; in non-recurrent cases increased normal protein may have a beneficial effect as p53 is involved in DNA damage repair.…”
Section: Discussionsupporting
confidence: 67%
“…The anticancer activity of p53 is through several mechanisms: it activates DNA repair proteins, induces growth arrest at the G1/S regulation point through p21 or initiates apoptosis if the DNA damage is irreversible [12]. It has been investigated also in meningioma and several studies showed a positive correlation with the grade and tumour recurrence [4,7,8,14,15,24,26], whereas authors reported the grade as an independent predictive factor of recurrences with high Mib1 and p53 LI being a supportive marker helpful in borderline cases [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation of p53 gene results in metabolically stable abnormal protein that accumulates in the nucleus reaching the level to be easily detected by immunostains. Expression of p53 protein in tissue section is an indicator of possible mutation in p53 gene itself [10,11]. In the present study, we aimed to investigate the immunohisto-chemical profile of meningiomas by using Ki-67 and p53 as markers with established roles in tumor progression and to determine the association of these markers with histological grade and subtype.…”
mentioning
confidence: 99%
“…The role of p53 has already been examined in the meningiomas: some of the examinations ended with negative or equivocal findings [43,[48][49][50], but some of them showed a significant correlation between the p53 status and the grade or recurrence of the tumour [4,7,8,19,20,28,37,41,44,46,57]. It is also described that p53 immunopositive cells are more frequent in the perinecrotic areas of post-embolised cases than in preserved parts of the tumour [39].…”
Section: Introductionmentioning
confidence: 99%